Optimization of the Formula of Hand Sanitizer Preparation of Teak Leaf Extract (Tectona grandis) as an Antibacterial - Nafisah Isnawati (LPPM Universitas dr. Soebandi, 2024)
Background: One of the major causes of diarrhea is the bacterium Escherichia coli. This bacterium is commonly found on the palms of hands. To address diarrhea, prevention is necessary, one of which is by using ethanol extract of teak leaves (Tectona grandis). Teak leaves (Tectona grandis) contain secondary metabolites such as flavonoids, saponins, tannins, steroids, and triterpenoids that act as antibacterial agents. Purpose: This study aims to determine that the ethanol extract of teak leaves (Tectona grandis) can be formulated into a hand sanitizer with antibacterial properties Methods: The design of this research study is laboratory experimental, with the process of making extracts, formulating them, evaluating the physical quality of preparations, and performing antibacterial tests. The extract was made using the maceration method with 70% ethanol solvent. Hand sanitizer preparations for teak leaf extract (Tectona grandis) are formulated with three concentrations, namely 10%, 12%, and 15%. Results: The results of the organoleptic evaluation showed a medium to dark brown color, with a semi-solid texture and a characteristic teak leaf aroma. The homogeneity test results showed that all formulations were homogeneous. The pH test results were 7.06 for F1, 7.11 for F2, and 7.12 for F3. The spreadability test results were 5.09 cm for F1, 5.42 cm for F2, and 5.14 cm for F3. The adhesion test results were 10.34 seconds for F1, 9.53 seconds for F2, and 12.71 seconds for F3. The viscosity test results were 2,867 cps for F1, 2,567 cps for F2, and 2,611 cps for F3. The antibacterial activity test showed that the hand sanitizer had antibacterial activity with extract concentrations of 10%, 12%, and 15%. The inhibition zone diameters were 12.67 mm for F1, 15 mm for F2, and 21.67 mm for F3. Conclusions: The ethanol extract of teak leaves (Tectona grandis) can be formulated into an emulgel hand sanitizer with antibacterial properties against Escherichia coli, and all three formulations meet the preparation evaluation requirements. The best formula was at a 15% concentration with an inhibition zone of 21.67 mm.